Proceedings. RTAS 2004. 10th IEEE Real-Time and Embedded Technology and Applications Symposium, 2004.
DOI: 10.1109/rttas.2004.1317259
|View full text |Cite
|
Sign up to set email alerts
|

Speeding up string matching over compressed text on handheld devices using tagged sub-optimal code (TSC)

Abstract: Tagged Sub-optimal code (TSC) is a new coding technique presented in this paper to speed up string matching over compressed databases on PDAs. TSC is a variable-length sub-optimal code that supports minimal prefix property. It always determines its codeword boundary without traversing a tree or lookup table. TSC technique may be beneficial in many types of applications: speeding up string matching over compressed text, speeding decoding process, as well as any general-purpose integer representation code. Exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…In another study [12], we found that using Tagged Suboptimal Code (TSC) on handheld devices could speed up string matching over compressed databases and avoid compression delay.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study [12], we found that using Tagged Suboptimal Code (TSC) on handheld devices could speed up string matching over compressed databases and avoid compression delay.…”
Section: Related Workmentioning
confidence: 99%
“…Two solutions to compress the entire database and keeps it accessible and manageable while it is on compressed form are introduced in our previous work [10,12], and can be used with SCTB and SCTT algorithms. Therefore, compression is done by compressing each record individually and retains the record references structure within the database unbroken.…”
Section: Handheld Data Files Organizationmentioning
confidence: 99%
“…To resolve the space-efficiency dilemma, some other methods have been proposed, in which text or index pre-processing means were developed. These methods, including a hybrid sorting algorithm [10], augmented suffix arrays [11], compression [12][13] [14], and coding techniques, such as Huffman coding [15] and Tagged Sub-optimal Code [16], have made great efforts for reducing the space-efficiency barrier.…”
Section: Introductionmentioning
confidence: 99%